2018
DOI: 10.1530/jme-18-0094
|View full text |Cite
|
Sign up to set email alerts
|

Hormone therapy and breast cancer: emerging steroid receptor mechanisms

Abstract: Although hormone therapy is widely used by millions of women to relieve symptoms of menopause, it has been associated with several side-effects such as coronary heart disease, stroke and increased invasive breast cancer risk. These side-effects have caused many women to seek alternatives to conventional hormone therapy, including the controversial custom-compounded bioidentical hormone therapy suggested to not increase breast cancer risk. Historically estrogens and the estrogen receptor were considered the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 311 publications
(546 reference statements)
0
11
0
1
Order By: Relevance
“…MHT was weakly associated with lower serum levels of IGFBP7 in a subset of patients in the same cohort ( 35 ). The IGF/insulin and ER pathways, through which MHT mainly functions, are interconnected in breast cancer ( 13 , 36 ). A previous study based on the same breast cancer cohort reported that MHT was associated with lobular cancer and low histological grade ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…MHT was weakly associated with lower serum levels of IGFBP7 in a subset of patients in the same cohort ( 35 ). The IGF/insulin and ER pathways, through which MHT mainly functions, are interconnected in breast cancer ( 13 , 36 ). A previous study based on the same breast cancer cohort reported that MHT was associated with lobular cancer and low histological grade ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Progestins often elicit biological effects that are distinct from each other and natural P 4 [reviewed in ( 2 , 44 , 45 )]. Indeed, it is known that some progestins have been linked to increased breast cancer risk, while oral micronized P 4 has not [reviewed in ( 14 , 17 )].…”
Section: Resultsmentioning
confidence: 99%
“…Although taking CEE alone will not increase the incidence of breast cancer and HT will not increase the breast cancer mortality over time, HT should not be used for the sole purpose of reducing the risk of breast cancer risk because of complicated factors related to it (24,25). Estrogen-progestogen combinations are related to a higher risk of breast cancer compared to estrogenonly preparations, which indicates that the progestogen component is possibly the reason for the increased risk (90,91). The risk also increased with a longer duration of HT.…”
Section: Breast Cancer and Endometrial Cancermentioning
confidence: 99%